Prevalence of zoonotic visceral leishmaniasis in dogs in an endemic area of Brazil - Danillo de Souza Pimentel; Rafael Antonio Nascimento Ramos; Marília de Andrade Santana; Carina Scanoni Maia; Gílcia Aparecida de Carvalho; Hernande Pereira da Silva; Leucio Câmara Alves (Revista da Sociedade Brasileira de Medicina Tropical, 2015)
INTRODUCTION: The northeast region of Brazil is endemic for zoonotic visceral leishmaniasis (ZVL). The aim of this study was to determine the prevalence of infection in dogs in Petrolina. METHODS: Blood samples were collected from dogs (n = 600), and bone-marrow biopsy was performed in animals with positive serological test results that presented clinical signs of ZVL. The serological analyses were performed using an enzyme-linked immunosorbent assay (ELISA) (S7(r)Biogene). RESULTS: Of the 600 dogs tested, 19% (115/600) presented anti-L. infantum chagasi antibodies. CONCLUSIONS: Our data are important because canine infection is an important risk factor for the human disease.